Assessment of Sintering of Fly Ash in a Circulating Fluidised Bed Combustor - French, D.; Vuthaluru, Hari (EMS Energy Institute, 2013)
This paper describes a comparative study of ash deposition in two 125 MWe circulating fluidised bed combustor power generation plants (CFBC 1 and CFBC 2) undertaken to provide a comparative data for the identification of the possible causes of ash deposition in CFBC 2. Samples of the feed coal, limestone, deposits and ashes were collected from various sampling points within the furnace and from areas of ash deposition. The samples were analysed using a combination of ash chemistry and quantitative X-ray diffraction analysis, optical petrography and QEMSCAN analysis. Although the results indicated that the nature of the superheater deposits in both power plants is similar in terms of mineralogy and texture (dominated by iron oxide and anhydrite occurring as layers), the ash chemistry and mineralogy are both significantly different. The study confirmed that CFBC 2 ashes are unusual in the occurrence of complete sulphation of the decarbonated limestone with no evidence of either the occurrence of intermediate phases such as CaO or the presence of sulphate reaction rims on decarbonated limestone as observed for CFBC 1 ashes and commonly described in the literature. A possible reason for this unusual behaviour is the high sulphur content of feed coal in CFBC 2 leading to complete sulphation of limestone due to an insufficient feed rate. Another possible factor is the greater proportion of fine particles in the milled CFBC 2 limestone which would react completely. This observation is supported by the occurrence of fine anhydrite particles in the CFBC 2 back pass sample and a subsequent increase in grain size in the back end of the boiler, suggesting that winnowing of the fine particles has occurred in the hotter sections of the back pass. This is in contrast to the relatively limited size variation exhibited by anhydrite in the ash samples of CFBC 1.